2021
DOI: 10.3389/fpsyg.2021.697703
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Prediction of the School Psychological Capital Among Chinese College Students

Abstract: This study validated the school psychological capital (PsyCap) scale in the Chinese context and examined the predictive effect of PsyCap resources on academic engagement and achievement emotions. Self-report data for PsyCap resources, student engagement, enjoyment, anxiety, and boredom toward English learning were collected from 1,000 sophomores. Item-level analyses and confirmatory factor analysis were used to verify the validity of the school PsyCap scale, and structural equation modeling was applied to reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 73 publications
4
10
0
Order By: Relevance
“…Based on our findings, the cognitive resources of students, PsyCap has shown a positive effect on academic engagement behavior, another form, and a source of growth and learning for students. Our findings also supported this theoretical assumption and are also consistent with prior literature ( Luthans et al, 2012 ; Carmona-Halty et al, 2021 ; Kang et al, 2021 ; Saman and Wirawan, 2021 ). Keeping this perspective in view, it can be suggested that the accumulation of positive psychological resources in the form of PsyCap can help individuals to enhance their performance not just in academics ( Luthans et al, 2014 ) but in general occupational settings as well ( Luthans et al, 2007b , 2012 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on our findings, the cognitive resources of students, PsyCap has shown a positive effect on academic engagement behavior, another form, and a source of growth and learning for students. Our findings also supported this theoretical assumption and are also consistent with prior literature ( Luthans et al, 2012 ; Carmona-Halty et al, 2021 ; Kang et al, 2021 ; Saman and Wirawan, 2021 ). Keeping this perspective in view, it can be suggested that the accumulation of positive psychological resources in the form of PsyCap can help individuals to enhance their performance not just in academics ( Luthans et al, 2014 ) but in general occupational settings as well ( Luthans et al, 2007b , 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…With the advent of positive psychology, its application has seen tremendous growth in different industrial sectors, be it production, services, or even the educational sector ( Avey et al, 2010 ; He et al, 2019 ; Carmona-Halty et al, 2021 ; Kang et al, 2021 ; Saleem, 2022 ). For the educational sector, contemporary research has witnessed the augmentation of students’ academic engagement through their positive emotions and positive psychology ( Carmona-Halty et al, 2021 ; Dewaele and Li, 2021 ; Luthans et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most influential countries in terms of production were China with 61 documents ( Bi and Jin, 2021 ; Cui, 2021 ; Kang et al., 2021 ; Shan et al., 2021 ; Xu and Zhang, 2021 ), followed by Spain, United Kingdom, Australia and United States with 10, 10, 8, 8 documents respectively. As for institutions of affiliation of the authors, the universities of Curtin, Tilburg, Jaume I and of Arts and Sciences of Chongqing stand out.…”
Section: Resultsmentioning
confidence: 99%
“…These human resource management must contribute something beyond technological skills, academic talents, contacts, and networking (social capital) to the table; they must also contribute strong psychological capital to the table. As a result, if the main purpose of higher education is to equip our students to be successful in the workforce, we must move beyond teaching technical and intellectual skills to focus on the development of a person’s positive psychological capital ( Luthans et al, 2013 ; Onivehu, 2020 ; Kang et al, 2021 ). In the current scope of our study, it was assumed that academic psychological capital could aid in the relationship between teachers’ self-efficacy and employee-based brand equity.…”
Section: Introductionmentioning
confidence: 99%